Vexillata liomyos (Nemata: Ornithostrongylidae) de Liomys irroratus (Rodentia: Heteromyidae) de Sierra de Monte Negro, Morelos, México - Ortíz-Villaseñor, Ana Luisa; Eslava Araujo, Ariadna; Lozano García, Marco Antonio (Instituto de Ecología, A.C., 2011)
In a study to determine the rodent helminthfauna Liomys irroratus the subject area of Monte Negro Sierra, Morelos, Mexico, described the nematode Vexillata liomyos being the first report to the state, which extends its geographical distribution.